2017
DOI: 10.1002/jbm.a.36301
|View full text |Cite
|
Sign up to set email alerts
|

Functional self‐assembled peptide scaffold inhibits tumor necrosis factor‐alpha‐induced inflammation and apoptosis in nucleus pulposus cells by suppressing nuclear factor‐κB signaling

Abstract: Although nucleus pulposus (NP) tissue engineering has achieved tremendous success, researches still face the huge obstacles in maintaining cell survival and function. A novel functional self-assembled peptide RADA-KPSS was constructed by conjugating BMP-7 short active fragment (KPSS) to the C-terminus of RADA16-I that displays anti-inflammatory and anti-apoptosis effects. However, whether this functional self-assembled RADA-KPSS peptide can alleviate inflammation and NPC apoptosis induced by tumor necrosis fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A previous study by Li et al showed that TNF‐α induces apoptosis in NP cells. Zhang demonstrated that lentiviral shRNA silencing of CHOP partly suppressed disc cell apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study by Li et al showed that TNF‐α induces apoptosis in NP cells. Zhang demonstrated that lentiviral shRNA silencing of CHOP partly suppressed disc cell apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…TNF-α can enhance matrix-degrading enzyme activity and increase NP cell apoptosis (17,22,23). Li et al also reported that TNF-α induced NP cell inflammation and apoptosis by activating NF-κB signalling (24). Heme oxygenase-1 (HO-1) has also been reported to participate in the cellular anti-inflammatory processes relating to IVD degeneration (25).…”
Section: Introductionmentioning
confidence: 99%
“…to promote cell migration, proliferation, and differentiation (Li et al, 2017;Liu et al, 2013). In addition, these functionalized self-assembling peptide nanofibre scaffolds have been reported to exhibit extensive potential for bone, vascular, and neural regeneration (Bradshaw et al, 2014;Maleki, Natalello, Pugliese, & Gelain, 2017;Wang et al, 2015).…”
mentioning
confidence: 99%